Analisis Komunikasi Publik Perbankan Indonesia dalam Mewujudkan Program Ekonomi Berkelanjutan - Agus Prakarsa; Manik Sunuantari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study analyzes the sustainability communication strategies of key actors in Indonesia, consitstsof Bappenas, the Financial Services Authority (OJK), Bank Mandiri, and Bank Central Asia (BCA). The research examines how each institution formulates and manages communication related to sustainable finance and assesses the alignment of these practices with Stakeholder Theory and Excellence Theory. Using a qualitative approach, the study employs qualitative content analysis and comparative document analysis of SDGs communication guidelines, sustainable finance roadmaps, regulations, annual reports, and sustainability reports. The findings reveal that sustainability communication in Indonesia remains fragmented. Bappenas provides a macro-level and normative communication framework but lacks operational stakeholder segmentation. OJK adopts a primarily one-way communication model centered on regulatory dissemination, with limited mechanisms for public engagement. At the industry level, Bank Mandiri demonstrates a more advanced approach, supported by a dedicated ESG unit and comprehensive stakeholder mapping, whereas BCA integrates ESG issues into broader corporate communication, resulting in a more compliance-oriented practice. The study concludes that organizational structure, communication models, and stakeholder management strongly influence the effectiveness of sustainability communication. Strengthening cross-actor harmonization and enhancing dialogic, two-way communication are recommended to improve Indonesia’s national sustainability communication ecosystem.